Before Words. Music and Its Natural History (De Musica, 2024)
The paper investigates the evolutionary origins of music, focusing on its adaptive function and phylogeny. We compares theories such as Steven Pinker's, who sees music as a non-adaptive by-product, Charles Darwin's ideas that music evolved through sexual selection as a signal of intelligence and fitness, and Herbert Spencer's, who argued that music evolved from emotional expression rather than reproduction. Other perspectives highlight the role of music in social cohesion and emotional expression. The paper also examines modern research that questions whether sexual selection is the sole driver of evolution, suggesting a complex and multidisciplinary understanding of the role of music in human evolution.